Mechanized transplanting of rice (Oryza sativa L.) in nonpuddled and no-till conditions in the rice-wheat cropping system in Haryana, India. - Kamboj, Baldev Raj; Yadav, Dharam Bir; Yadav, Ashok; Goel, Narender Kumar; Gill, Gurjeet; Malik, Ram K.; Chauhan, Bhagirath Singh (Scientific Research Publishing, Inc., 2013)
The common practice of establishing rice in the rice-wheat system in India is manual transplanting of seedlings in the puddled soil. Besides being costly, cumbersome, and time consuming, puddling results in degradation of soil and the formation of a hard pan, which impedes root growth of subsequent upland crops. In addition, decreased availability and increasing cost of labor have increased the cost of rice cultivation through conventional methods. Because of these concerns, there is a need for mechanized transplanting of rice which is less labor-intensive and can ensure optimum plant population under nonpuddled and/or no-till conditions. A large number of on-farm trials were conducted at farmers’ fields in Haryana, India, from 2006 to 2010 to evaluate the performance of the mechanical transplanted rice (MTR) under nonpuddled and no-till situations as compared to conventional puddled transplant rice (CPTR). Compared with CPTR, nonpuddled MTR produced 3%-11% higher grain yield in different years. Rice cultivars, viz. HKR47, HKR127, PR113, PR114, PB1, PB1121, CSR30, and Arize6129, performed consistently better under nonpuddled MTR as compared to CPTR. Performance of different cultivars (PR113, PR114, HKR47, and Pusa 44) was also better under no-till MTR as compared to CPTR. The “basmati” cultivar CSR30 performed equally in no-till MTR and CPTR systems. The results of our study suggest that rice can be easily grown under nonpuddled and no-till conditions with yield advantages over the CPTR system. Even in the case of similar yield between CPTR and MTR systems, the MTR system will help in reducing labor requirement and ultimately, will increase overall profits to farmers.